Location variables and their relative effect on gross rentals of neighbourhood, community and regional shopping centres in South Africa - Morphis, Andreas (My University, 2012)
The ability to conceptualise and understand the impact of location variables on a retailer’s performance is crucial to stakeholders such as the owners of, and lenders to income-generating properties (Ownbey, Davis and Sundel, 1994). This research investigates the importance placed on nine location variables and how they differ regarding the success of neighbourhood, community and regional retail shopping centres. The results and outcomes of this study offer the various stakeholders an advantage and insight into their decision making when analysing the performance ability of different categories of retail shopping centres in South Africa. Quantitative research was used to identify the varying influences that location variables have on the ability of different categories of retail shopping centres to perform. The results indicate that the location variables have different levels of significance and importance depending on which category of retail shopping centre one investigates. The supermarket anchor is the most significant location variable for each of the retail shopping centres. The study revealed that the visibility of tenants’ signs from the primary street and supermarket parking lot to be the most insignificant variable.
MBA thesis - WBS
Keywords: Shopping centres; Location of shopping centres; Location variables